Multi-domain feature joint optimization based on multi-view learning for improving the EEG decoding - Shi, Bin; Yue, Zan; Yin, Shuai; Zhao, Junyang; Wang, Jing (Frontiers in Human Neuroscience, 2023)
Background: Brain-computer interface (BCI) systems based on motor imagery (MI) have been widely used in neurorehabilitation. Feature extraction applied by common spatial pattern (CSP) is very popular in MI classification. The effectiveness of CSP is highly affected by the frequency band and time window of electroencephalogram (EEG)segments and channels selected.Objective: In this study, the multi-domain feature joint optimization (MDFJO) based on multiview learning method is proposed, which aims to select the discriminative features enhancing the classification performance.The channel patterns are divided by fisher discriminant criterion (FDC). Furthermore, the raw EEG is intercepted for multiple sub-bands and time intervals signal. The high-dimensional features are constructed by extracting features from CSP on each EEG segment. Specifically, the multi-view learning method is used to select the optimal features, and the proposed feature sparsification strategy on the time level is proposed to further refine the optimal features. Results: Two public EEG datasets are employed to validate the proposed MDFJO method. The average classification accuracy of the MDFJO in data 1 and data 2 is 88.29% and 87.21%, respectively. The classification result of MDFJO was significantly better than MSO (p<0.05), FBCSP32 (p<0.01) and other competing methods (p<0.001).Compared with the CSP, SFBCSP and FBCSP method with channel number 16, 32 and all channels as well as MSO, the MDFJO significantly improves the test accuracy. The feature sparsification strategy proposed in this article can effectively enhance the classification accuracy.The proposed method could improve the practicability and effectiveness of the BCI system.